2017
DOI: 10.1016/j.jhin.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Management and cost of surgical site infection in patients undergoing surgery for spinal metastasis

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 21 publications
1
20
0
5
Order By: Relevance
“…на основании проведенного анализа полученных данных было выделено семь значимых факторов (р<0,05): сахарный диабет, послеоперационная ликворея, определенный класс по шкалам ASA (3, 4) и ECOG (2,3,4), объем кровопотери, продолжительность операции и тип противоопухолевой терапии. Однако наибольшую статистическую значимость (р<0,01) имеют три последних показателя: операционные факторы (объем кровопотери и продолжительность операции) и тип противоопухолевой терапии.…”
Section: таблица 3 анализ качественных факторов риска в группах с помunclassified
See 3 more Smart Citations
“…на основании проведенного анализа полученных данных было выделено семь значимых факторов (р<0,05): сахарный диабет, послеоперационная ликворея, определенный класс по шкалам ASA (3, 4) и ECOG (2,3,4), объем кровопотери, продолжительность операции и тип противоопухолевой терапии. Однако наибольшую статистическую значимость (р<0,01) имеют три последних показателя: операционные факторы (объем кровопотери и продолжительность операции) и тип противоопухолевой терапии.…”
Section: таблица 3 анализ качественных факторов риска в группах с помunclassified
“…Шкалы ASA и ECOG подтверждают свою прогностическую ценность относительно общего состояния онкологического пациента [3,6,10].…”
Section: таблица 3 анализ качественных факторов риска в группах с помunclassified
See 2 more Smart Citations
“…Despite a further advancement of our understanding of the incidence, clinical consequences, and methods to reduce SSIs associated with implantable pain therapies, relatively little is known about the associated economic costs of an implantable pain therapy infection . In other specialties, it has been demonstrated that SSIs can lead to significant economic burden on the healthcare system . The purpose of this study is to evaluate the infection rate for SCS implants and its economic burden on the healthcare system by examining the cost and healthcare utilization associated with infection in a large United States payer database.…”
Section: Introductionmentioning
confidence: 99%